2018
DOI: 10.1007/s00296-018-3995-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of low-dose vs high-dose cyclophosphamide regimen as induction therapy in the treatment of proliferative lupus nephritis: a single center study

Abstract: The study was registered at http://www.clintrials.gov . NCT02645565.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…80 Importantly, the low-dose CY regimen (ELNT) was tested also in non-exclusively Caucasian populations, with similar results. 10 13 14 65 Regarding the use of CNI or ‘multitarget’ therapy (combination of CNI with MMF), it is important to point out that the majority of studies (both randomised and observational) testing this class of drugs have used TAC, hence the respective clarification in the manuscript of the updated EULAR/ERA-EDTA recommendations. 55 The scepticism raised by the fact that initial studies using the multitarget regimen were performed in Asian populations has been partly addressed by the multi-ethnic phase II study of voclosporin/MMF combination 20 ; the results of the phase III study, which recently announced positive results, are expected to provide more data regarding a possible future universal recommendation of multitarget regimens for LN.…”
Section: Discussionmentioning
confidence: 99%
“…80 Importantly, the low-dose CY regimen (ELNT) was tested also in non-exclusively Caucasian populations, with similar results. 10 13 14 65 Regarding the use of CNI or ‘multitarget’ therapy (combination of CNI with MMF), it is important to point out that the majority of studies (both randomised and observational) testing this class of drugs have used TAC, hence the respective clarification in the manuscript of the updated EULAR/ERA-EDTA recommendations. 55 The scepticism raised by the fact that initial studies using the multitarget regimen were performed in Asian populations has been partly addressed by the multi-ethnic phase II study of voclosporin/MMF combination 20 ; the results of the phase III study, which recently announced positive results, are expected to provide more data regarding a possible future universal recommendation of multitarget regimens for LN.…”
Section: Discussionmentioning
confidence: 99%
“…34 The 10-year Euro-Lupus Nephritis Trial data showed equal efficacy of low-dose versus high-dose CY, 24 and the low-dose regimen has been used in non-European populations. [35][36][37][38] Consequently, both MMF/MPA and low-dose CY are recommended as firstline options for initial (induction) treatment. The recommended target dose of MMF is now changed to 2-3 g/day (MPA 1.44-2.16 g/day), based on evidence that therapeutic drug dosage may range between 1 and 3 g/day.…”
Section: Initial Treatmentmentioning
confidence: 99%
“…There is a paucity of data on the ovarian toxicity of modified NIH regimens of CYC. A 6-month randomised controlled trial from the Indian subcontinent compared modified NIH and Euro-Lupus regimens in lupus nephritis and found the rates of sustained amenorrhoea to be 5% and 2% in the two arms, respectively [ 14 ]. In our study, the rate of sustained (> 12 months) amenorrhoea with CYC was 4% but no premature ovarian failure was observed at a mean cumulative dose of 4.6 ± 1.8 g.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of CYC through intravenous route at lower doses for a shorter duration, and development of better markers of ovarian reserve, the incidence of ovarian toxicity with CYC needs reassessment. There is limited data on gonadal toxicity with CYC use in the current era where modified National Institute of Health (NIH) regimens (employing azathioprine or MMF instead of quarterly CYC pulses for maintenance after the initial 6 monthly pulses) or low-dose Euro-Lupus regimen are used [ 13 , 14 ]. Additionally, the possible negative impact of underlying SLE on ovarian function is an important confounding factor that needs to be taken into consideration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%